Post-tonsillectomy Hemorrhage in Patients Receiving Ketorolac Analgesic - Yadav, D; Dangol, B; Shrestha, N; Pandit, S; Nepal, A (Kathmandu University Medical Journal, 2023)
Background Ketorolac, the non-steroidal anti-inflammatory drug, is thought to have less sedation as well as postoperative nausea and vomiting in comparison to opioids, but with higher risk of post-tonsillectomy hemorrhage as reported in some of the literatures. There is no consensus till date in the use of ketorolac in the management of pain following tonsil and adenoid related surgeries. Objective To find out the incidence of hemorrhage following tonsil and adenoid related surgeries in patients receiving ketorolac in postoperative period. Method This is a retrospective chart review of patients undergoing tonsil and adenoid related surgeries who had received ketorolac during April, 2013 to May, 2019 at department of ENT-HNS, Patan Academy of Health Sciences (PAHS), Lalitpur, Nepal. Post-tonsillectomy hemorrhage rate was calculated in pediatric and adult patients. Result During the study period, 103 patients (male – 50 and female – 53) received ketorolac in postoperative period. Tonsillectomy and adenotonsillectomy were performed in 71and 32 patients respectively. Forty-five patients were < 18 years whereas 58 were ≥ 18 years. Most common indication for surgery was recurrent tonsillitis (66/103) followed by adenotonsillar hypertrophy (31/103). Post-tonsillectomy hemorrhage was observed in 15 patients; among them, four out 45 were < 18 years and 11 out of 58 ≥ 18 years. All five patients out of 15, who required surgical intervention for post-tonsillectomy hemorrhage, were ≥ 18 years and were operated for recurrent tonsillitis. Rest of the patients (10/15) were managed conservatively. None of the patients required blood transfusion. Conclusion Ketorolac is not associated with increased risk of post-tonsillectomy hemorrhage in children and can safely be administered. Whereas in adults, recurrent tonsillitis being the most common indication for tonsillectomy, it should be used cautiously.